The Use Maru Video Tutorials to Improve Skills Make Dowry from Paper Money for Children with Hearing Impairment - Jehan Nabela Oktaviani (Department of Special Education, 2022)
Children with hearing impairment aside from being taught academically need to acquire a set of skills, such as making dowry from paper money. This study, created a learning media to teach dowry from paper money, using video tutorials MARU . MARU tutorial video contains an explanation video about the names of tools, materials, how to make a dowry from paper money containing a sign language system and reading text so children with hearing impairment can understand the contents of MARU tutorial video. This study aims to prove the effect of using MARU video tutorials on improving the skills of making dowry from paper money children with hearing impairment grade XI. This study use a quantitative approach with experimental research methods, and using the one group Pretest-Posttest design. The instrument used is a multiple choice test. The sample in this study was seven children with hearing impairment grade XI at certain Special education school in bandung. The values of the pretest and posttest were processed and compared using the Wilcoxon Test to test the research hypothesis. The results of this study indicate that the MARU video tutorial can improve the skills of making dowry from paper money in Children with hearing Impairment. The results concluded that the MARU video tutorial can be used as a learning medium in learning to make dowry from paper money.